Assessment of employee wellness programme utilisation in the Department of Transport and Community Safety, Limpopo Province - Ramokgola, Motlalepule Peter (My University, 2023)
Background: Employee Wellness Programmes (EWPs) is a comprehensive health initiative which is a strategy to maintain and improve the well-being of employees. EWPs are profoundly helpful in ensuring that the wellbeing of employees is taken care of. The programme can be assessed by the programme developers to ensure that the programme remains responsive to rapidly changing educational and healthcare settings. The evaluation of EWPs has greater potential to influence its utilisation by employees. This study sought to understand and document employee wellness programme utilisation in the Department of Transport and Community Safety. Objectives: To explore and describe employee wellness programme utilisation in the Department of Transport and Community Safety in Limpopo Province. Methods: The study used the qualitative research approach. Participants of the study were full-time employees at the Department of Transport and Community Safety. Data was collected through semi-structured interviews and the sample size was 15 participants which was determined by saturation of data. Data was analysed through Thematic Content Analysis. Results: Lack of wellness programme utilisation among employees and identified cases of chronic illness, insufficient physical activity and those case that are stress related amongst employees which were received at EWP component are associated with lack of understanding for the programme. The study provides a useful qualitative enquiry of employees at Department of Transport and Community Safety about the programme utilisation. Conclusion: Many employees have concluded that Employee Wellness Programmes intent to enhance and maintain the well-being of employees. However, in Department of Transport and Community Safety (DTCS), there is a serious need for strengthening the implementation of EWPs to improve utilisation.
Thesis (MPH.) -- University of Limpopo, 2023
Keywords: Employees; Wellness Programme; Assessment; Programme utilisation; Employee health promotion; Government employees